Assessment of Non-Coding RNAs (miR-506 and circRNA 000284) and their Target Gene SNAIL-2 in Breast Tumors: Implications for Prognosis and a Possible Circulating Biomarker - Mahdieh Salimi; Shamim Dashti Gohari (Basic & Clinical Cancer Research, 2024)
Breast cancer is the most common malignancy among women, and early diagnosis and targeted therapy have garnered significant attention. Non-coding RNAs have emerged as potential diagnostic, prognostic, and treatment biomarkers for breast cancer. This study aimed to evaluate the expression of non-coding RNAs, specifically miR-506 and circular RNA 000284, and their target gene SNAIL-2 in breast tumors compared to normal controls. The study also focused on clinicopathological characteristics, and plasma was monitored for expression of circ0000284 to identify a possible accessible cancer-related marker.